Heterogeneity in immune cell composition is associated with Mycobacterium tuberculosis replication at the granuloma level - Cooper, Sarah K.; Ackart, David Forrest; Lanni, Faye; Henao-Tamayo, Marcela; Anderson, G. Brooke; Podell, Brendan K. (Frontiers in Immunology, 2024)
The control of bacterial growth is key to the prevention and treatment of tuberculosis (TB).Granulomas represent independent foci of the host immune response that present heterogeneous capacity for control of bacterial growth. At the whole tissue level, B cells and CD4 or CD8 T cells have an established role in immune protection against TB. Immune cells interact within each granuloma response, but the impact of granuloma immune composition on bacterial replication remains unknown. Here we investigate the associations between immune cell composition, including B cell, CD4, and CD8 T cells, and the state of replicating Mycobacterium tuberculosis (Mtb) within the granuloma. A measure of ribosomal RNA synthesis, the RS ratioâ, represents a proxy measure of Mtb replication at the whole tissue level. We adapted the RS ratio through use of in situ hybridization, to identify replicating and non-replicating Mtb within each designated granuloma. We applied a regression model to characterize the associations between immune cell populations and the state of Mtb replication within each respective granuloma. In the evaluation nearly 200 granulomas, we identified heterogeneity in both immune cell composition and proportion of replicating bacteria.We found clear evidence of directional associations between immune cell composition and replicating Mtb. Controlling for vaccination status and endpoint post-infection, granulomas with lower CD4 or higher CD8 cell counts are associated with a higher percent of replicating Mtb.Conversely, changes in B cell proportions were associated with little change in Mtb replication. This study establishes heterogeneity across granulomas, demonstrating that certain immune cell types are differentially associated with control of Mtb replication. These data suggest that evaluation at the granuloma level may be imperative to identifying correlates of immune protection.